Pseudostatic analysis of soil nailed vertical wall for composite failure. Issue 2 (4th March 2022) - Muthukumar, Surya; Kolathayar, Sreevalsa; Valli, Asvitha; Sathyan, Dhanya
ABSTRACT: In the present study, pseudostatic method is used to analyse the stability of soil-nailed vertical wall under seismic conditions. This approach includes an additional inertial force equivalent to the dynamic load caused by earthquake. The soil surface which undergoes failure due to the static and dynamic condition is assumed to be a realistic composite failure surface rather than the conventional planar, circular or log-spiral surfaces. This study investigates the effect of various parameters such as vertical and horizontal seismic acceleration coefficients, friction angle of soil, shear wave velocity, primary wave velocity, amplification factor, nail length, spacing of the nails, and nail inclination on the stability of the vertical soil-nailed wall. A comparison study is made between the results obtained from the present analysis and the values reported in the literature. It is observed the present study with composite failure surface gives higher values of Factor of Safety compared to planar failure surface. Composite failure surface is more realistic and hence more accurate compared to a planar failure surface which gives a conservative value of Factor of Safety.